Water loss in transit in an intermittent river in brazilian semi-arid - Cristian Epifanio Toledo; Emanuelly de Moura Silva Almeida; Alexandre Vicente Lopes Neto; Thályta Lharyssa Gonçalves Rodrigues Gonçalves Rodrigues Silva; Filipe Augusto Rodrigues Santos (Agro@mbiente On-line)
Riverwater often comes into contact with the underground flow in aquifers. When this contact occurs, the river and aquifer are considered to be hydraulically connected. In recent decades, there has been great interest in trying to to improve understanding of the interactions occuring between superficial and subterranean water systems. A variety of analytical solutions have been proposed to describe the interaction of confined and free aquifers with adjacent rivers, including the quantification of the decrease of river flow along its course. The objective of the current study was to calibrate and validate a loss-in-transit flow model for rivers, and to evaluate the minimum flow that still permits connectivity between water sources in the Alto Jaguaribe basin. The methodology used was based on the equation of continuity and mass balance along the study river. A modified Araújo and Ribeiro equation showed strong applicability to loss-in-transit generation, with a mean loss in transit of 3.6% km-1, and a Nash and Sutcliffe Efficiency value of 0.29. On the other hand, the classbased loss of upstream flow generated 4 classes with a mean of 2.6% km-1 and showed great improvement, reaching an NSE of 0.74 - high efficiency. Minimum flows were below the regular flow recorded by the Ceará Secretariat of Water Resources, showing that the ability exists in the region hydrological connectivity between reservoirs in the Alto Jaguaribe basin and for alluvial aquifers to be recharged.